The Rough and Gone Town of Ladore, Kansas - Mog, Christy (Kansas State University. Dept. of History, 2011)
In southern Neosho County, the "wild west" community of Ladore flourished between 1869 and 1901, when its post office closed. Early events including gambling and lynchings stamped the town with a legendary character. The author writes an engaging portrait of this vanished town and provides maps and photographs as well as concrete newspaper accounts. She explores the intriguing origins of its name. Ladore died when the M,K and T railway abandoned the proposed depot there.
Keywords: Neosho County; Ladore; M.K. & T Railroad; Lynchings; Wild West